2006
DOI: 10.1016/j.jvs.2006.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Early and late complications of silicone patch saphenoplasty at the saphenofemoral junction

Abstract: Patch saphenoplasty can cause early and late postoperative complications in the groin, which are usually minor. In exceptional cases, major complications may cause important morbidity and may be difficult to handle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…18 Complications occurred in 19.5% of limbs after redo surgery, of which half were lymphatic in nature. 19 This non-randomized study showed a benefit for the use of silicone patch saphenoplasty, but the groups were later used as historical controls in a further study examining the benefit of closure of the cribriform fascia after SFJ ligation for primary varicose veins. 20 Closure of the cribriform fascia was then proposed as an alternative option to prevent postoperative neovascularization as this was reduced at one year.…”
Section: Closing the Groin Dissectionmentioning
confidence: 99%
“…18 Complications occurred in 19.5% of limbs after redo surgery, of which half were lymphatic in nature. 19 This non-randomized study showed a benefit for the use of silicone patch saphenoplasty, but the groups were later used as historical controls in a further study examining the benefit of closure of the cribriform fascia after SFJ ligation for primary varicose veins. 20 Closure of the cribriform fascia was then proposed as an alternative option to prevent postoperative neovascularization as this was reduced at one year.…”
Section: Closing the Groin Dissectionmentioning
confidence: 99%
“…Eine "Barriere" im Bereich des Hiatus saphenus, wie vielfach vorgeschlagen [46,47], kann sicherlich eine bestimmte Anzahl von Neubildungen und damit Rezidive verhindern, allerdings ist auch mit einer nicht unerheblichen Rate lymphologischer Komplikationen zu rechnen [48], da hier jene efferenten Lymphgefäße der inguinalen Lymphknoten beeinträchtigt werden, die mit der ursprünglichen -V. saphena magna durch den Hiatus saphenus ziehen.…”
Section: Diskussionunclassified
“…Deep vein thrombosis, wound infection, lymphocele, and lymphoedema have been reported following silicone patch application [24]. No such untoward events have been reported in studies in which PTFE patch was used instead of silicone patch [15][16][17].…”
Section: Correlation Of Preoperative Clinical Severity Of Disease Witmentioning
confidence: 99%